2019
DOI: 10.1073/pnas.1908921116
|View full text |Cite
|
Sign up to set email alerts
|

Ca isotopes record rapid crystal growth in volcanic and subvolcanic systems

Abstract: Kinetic calcium isotope effects can be used as growth-rate proxies for volcanic and subvolcanic minerals. Here, we analyze Ca isotopic compositions in experimental and natural samples and confirm that large kinetic effects (>2‰) can occur during magmatic plagioclase crystallization. Experiments confirm theoretical predictions that disequilibrium isotope effects depend mainly on the rates for crystal growth relative to liquid phase Ca diffusivity (R/D). Plagioclase phenocrysts from the 1915 Mount Lassen rhyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…This implies that these samples record either (i) kinetic isotope fractionations or (ii) incorporation of isotopically distinct Ca-rich materials, not recorded by other samples. In volcanic systems, large kinetic isotope effects can result from Ca diffusion during rapid crystal growth 21 . This mechanism cannot explain the composition of NSB samples, however, because a negative shift in bulk magma δ 44 Ca would require rapid growth and removal of minerals where Ca is strongly incompatible, which (by definition) would have little effect on the Ca budget.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This implies that these samples record either (i) kinetic isotope fractionations or (ii) incorporation of isotopically distinct Ca-rich materials, not recorded by other samples. In volcanic systems, large kinetic isotope effects can result from Ca diffusion during rapid crystal growth 21 . This mechanism cannot explain the composition of NSB samples, however, because a negative shift in bulk magma δ 44 Ca would require rapid growth and removal of minerals where Ca is strongly incompatible, which (by definition) would have little effect on the Ca budget.…”
Section: Resultsmentioning
confidence: 99%
“…Calcium (~50 μg) is separated from aliquots of the dissolved samples and standards using established column chemistry methods adapted from UC-Berkeley 21 , 35 38 and modified for multi-collector inductively coupled plasma mass spectrometry (MC-ICP-MS) analyses 39 . Eichrom ® DGA resin is thoroughly washed by alternating between ultrapure water and 4 M HNO 3 several times overnight before loading into home-made Teflon columns with ~2 mL reservoirs.…”
Section: Methodsmentioning
confidence: 99%
“…CaI fractionation occurs during crystallization processes e.g. during volcanic eruptions [34] and during coral calcification in concert with endosymbiotic flagellates (ref). ….…”
Section: Discussionmentioning
confidence: 99%
“…Petrological studies and thermodynamic models have long indicated that crustal magmatic reservoirs (i.e., magma chambers) contain an abundance of crystal mush, where “mush” refers to a system with melt contained in a framework of crystals (Cashman et al., 2017; Marsh, 1989, 2013; Pritchard et al., 2018; Wieser et al., 2020). Crystals have thermal and geochemical importance, as they can alter the chemistry and thermal state of magma, and provide constrains on the thermal state and timescales of magma storage, ascent, and eruption (Antonelli et al., 2019; Bachmann & Huber, 2016; Cooper, 2019; Costa et al., 2020; Rummel et al., 2020; Singer et al., 2018; Sparks & Cashman, 2017). In recent decades, many research efforts have been devoted to understanding how crystal mush evolves and interacts with magma, using quantitative models and principles in thermodynamics, geochemistry, and geophysics.…”
Section: Background: Magma Chamber Model With Poroelastic/viscoelastic Mushmentioning
confidence: 99%